The Implementation of Problem Based Learning (PBL) Model in Thermochemistry to Enhance Concept Understanding in 11th Grade Science Students at SMAN 1 Anggaberi - Novriana, Dita Tri; Harimu, La; Haetami, Aceng (The Future of Education Journal, 2026)
This research aims to determine the description of students' concept understanding, effectiveness, and student responses to the application of the problem-based learning model on thermochemical  material for class XI MIA SMAN 1 Anggaberi. The sample in this study was class XI Mia, with a total of 18 students as the experimental class. The research method used was pre-experimental with a Pretest-Posttest Control Group Design. Data collection techniques used Pretest-Posttest, observation sheets, and questionnaires. The results showed that the learning outcomes of class XI MIA₂ students of SMAN 1 Anggaberi who were taught using the Problem Based Learning model obtained an average score of 83.33, student learning activities of 85.75%, and a response questionnaire of 71.30%. The N-gain analysis results showed that the problem-based learning model was significantly effective on student learning outcomes in the thermochemical system material at SMAN 1 Anggaberi, which was proven by the N-gain test analysis results with a value of 0.77.